SEXUALLY RISKY BEHAVIOR IN COLLEGE STUDENTS COMPARED TO RISKY BEHAVIOR IN OLDER WOMEN - Caico, Carol (European Scientific Journal, ESJ, 2015)
Objective: To explore the findings a study done about sexually risky behavior in College- Aged Students and compare with risky sexual behavior in older adults. Design: Descriptive study Setting: Commuter college Participants: A convenience sample of 770 students aged 15-25 Methods: To compare results of college sexual risks with a literature search of risky sexual behavior in older single, divorce and widowed women with identification of condom use and risks for sexually transmitted diseases. Results: The college study identified condom use to be 50.9% and 47.2% were not worried about getting HIV and 42.7% did not feel knowledgeable about STD’s. In the older population 71% did not use condoms and since returning to the sexual area after being widowed or divorced do not see themselves at risk for STD’s, yet the pathological changes of aging puts them at a higher risk for the development of STD’s. Conclusion: It is imperative that old as well as young be screened for all STD’s and conversation and education about sexual risks must be initiated by all health care providers . Education about sexual risks should be part of health education at a minimum starting in 9th grade for the young population.